Improper social distancing practices: sample cases in Indonesia - Santosa, Agus (MEDISAINS, 2020)
Social distancing is not always understood well by common people. The media's inaccurate information and the minimum of the government socialization create an excessive fear for specific groups. Then, the practices of social or physical distancing go beyond its real objectives